Illiterate apostles uneducated early Christians and the literates who loved them - Hilton, Allen R. (New York Bloomsbury Academic, 2018)
Cover -- Series -- Title -- Copyright -- Contents -- Part 1 The Cause of the Criticism -- Chapter 1 An Ethnography of Ancient Literacy -- An Anecdote -- Definitions -- Quantifying Literacy and Education -- Orality and Literacy -- Quantifying Ancient Literacy -- Early Christian Literacy -- The Social Impact of Literacy and Education -- Ancient Issues and Attitudes -- Attitudes toward Letters -- Attitudes toward the Lettered and Unlettered -- Notes -- Chapter 2 Attitudes toward the Illiterate -- Pagan Perception -- Lucian -- Galen -- Explicit Criticism -- Celsus -- Caecilius -- Implicit Criticism -- Justin -- Athenagoras -- Conclusion -- Notes -- Chapter 3 The Christians and the Schools -- Introduction -- Primary Education: Reading, Writing, and Arithmetic -- Secondary Education: Learning the Poets -- Higher Education: Speaking, Thinking, and Living Well -- Rhetorical Schools -- Philosophical Schools -- Exercise -- Imitation -- The Peril of the Pretender -- The Angle of the Apologists -- Notes -- Part 2 A First-Century Christian Reply -- Chapter 4 The Social Dynamics of Î ÎÎ¡Î¡ÎÎ£ÎÎ -- Introduction -- Î Î±ÏÏÎ·ÏÎ¯Î± Defined -- The Character of Î Î±ÏÏÎ·ÏÎ¯Î± as Speech -- Î Î±ÏÏÎ·ÏÎ¯Î± and Social Status -- Strategies for Safety -- Democracy and Friendship -- The Receptive Audience -- The Tolerable Speaker -- Acts 4 and the Social Dynamic Î Î±ÏÏÎ·ÏÎ¯Î± -- Conclusion -- Notes -- Chapter 5 The Virtue of Î ÎÎ¡Î¡ÎÎ£ÎÎ -- Î Î±ÏÏÎ·ÏÎ¯Î± as the Speech of the Courageous -- Î Î±ÏÏÎ·ÏÎ¯Î± and Education -- Training (á¼ÏÎºÎ·ÏÎ¹Ï) -- Example (ÏÎ±ÏÎ¬Î´ÎµÎ¹Î³Î¼Î±) -- The âPhilosophicalâ Setting of Acts 4 -- Philosophical Community -- A Philosophical Jesus -- A Philosophical Paul -- A Philosophical Peter -- Conclusion -- Notes -- Chapter 6 The âEducationâ of the Apostles -- The Power of the Spirit -- The Holy Spirit and Prophecy
The Holy Spirit and ÏÎ±ÏÏÎ·ÏÎ¯Î± -- The Example of Jesus -- Conclusion -- Notes -- Bibliography -- Index
Includes bibliographical references and index. Description based on print version record
Keywords: Christians-Books and reading-Rome; Church history-Primitive and early church, ca. 30-600; Literacy-Religious aspects-Christianity-History; Church History -- Primitive and early church, ca. 30-600; Christians -- Books and reading -- Rome; Literacy -- Religious aspects -- Christianity -- History; Electronic books; Books and reading; Christian literature, Early; Christians; Church History; Literacy